Dynamic characterization of small fibers based on the flexural vibrations of a piezoelectric cantilever probe. (27th June 2016) - Zhang, Xiaofei; Ye, Xuan; Li, Xide
Abstract: In this paper, we present a cantilever-probe system excited by a piezoelectric actuator, and use it to measure the dynamic mechanical properties of a micro- and nanoscale fiber. Coupling the fiber to the free end of the cantilever probe, we found the dynamic stiffness and damping coefficient of the fiber from the resonance frequency and the quality factor of the fiber-cantilever-probe system. The properties of Bacillus subtilis fibers measured using our proposed system agreed with tensile measurements, validating our method. Our measurements show that the piezoelectric actuator coupled to cantilever probe can be made equivalent to a clamped cantilever with an effective length, and calculated results show that the errors of measured natural frequency of the system can be ignored if the coupled fiber has an inclination angle of alignment of less than 10°. A sensitivity analysis indicates that the first or second resonant mode is the sensitive mode to test the sample's dynamic stiffness, while the damping property has different sensitivities for the first four modes. Our theoretical analysis demonstrates that the double-cantilever probe is also an effective sensitive structure that can be used to perform dynamic loading and characterize dynamic response. Our method has the advantage of using amplitude-frequency curves to obtain the dynamic mechanical properties without directly measuring displacements and forces as in tensile tests, and it also avoids the effects of the complex surface structure and deformation presenting in contact resonance method. Our method is effective for measuring the dynamic mechanical properties of fiber-like one-dimensional (1D) materials.